Kuzeydoğu Akdeniz’den Yakalanan Dikenli Vatoz (Raja clavata)’un Yumurta Kapsülleri ve Juvenilleri Görünürlüğü Üzerine bir Çalışma - Başusta, Nuri; Başusta, Asiye (Fırat University, 2019)
Bu çalışmada Kuzeydoğu Akdeniz’in uluslararası sularında yapılan ticari trol avcılığında 220-298 m arası derinlikten dikenli vatoz (Raja clavata Linnaeus, 1758) yumurta kapsülleri ve juvenilleri hedef dışı olarak toplanmıştır. Dikenli vatoza ait yumurta kapsülü ve juvenil bireyler bu bölgeden ilk kez tanımlanmıştır.

In this study, the egg capsules and juveniles of thornback skate, Raja clavata, were collected as by-catch from a commercial trawl fishing at depths between 220-298 m in the international waters of Northeastern Mediterranean Sea. Juvenile specimens and egg capsule of thornback skate were identified for the first time in this area
A Study on the Occurrence of Egg Capsule and Juvenile Individuals of Thornback Skate, Raja clavata, Captured from Northeastern Mediterranean Sea
Keywords: Engineering; Mühendislik